Zarys wojskowych dziejów Tomasza Mazowieckiego w latach II Rzeczypospolitej - Jarno, Witold (Przegląd Nauk Historycznych, 2015)
The article describes the history of the Polish Army garrison in Tomaszow Mazowiecki in years 1918–1939. In November 1918, the German infantry company was disarmed, what started the history of Polish garrison in this city. Quickly was formed a troop, which in January 1919 were incorporated into formed in Lodz the first Battalion of the 28th Infantry Regiment. In the summer of 1919 were moved from Brzeziny to Tomaszow: Military Replenishment Command and Field Replacement Battalion of the 30th Infantry Regiment. Year later arrived in the Tomaszow the second battalion of this regiment, which in 1924 was moved to Warsaw. In the same year arrived to Tomaszow the second Battalion of the 25th Infantry Regiment, which three years later was reorganized at the Reserve Officers Training Centre No. 4. This school existed until 1929. Then, for the next six years at Tomaszow didn’t stationed military units. Garrison was re-created in the autumn 1935. At the time, arrived in the city the second battalion of the 4th Heavy Artillery Regiment, which there stationed until the outbreak of war. This military unit was quartered in modern barracks built in the mid-thirties. In March 1939 the second battalion of the 4th Heavy Artillery Regiment was mobilized and directed to the Army „Lodz”. In the abandoned barracks was created reserve center, which existed until 5th September. Two days later Tomaszow Mazowiecki was occupied by the German army, what ended the history of Polish garrison in the interwar period.